Awareness of patients in the city of Belgrade about herbal products - Jovanović, Aleksandar; Stefanović-Vojinović, Jelena; Kukić-Marković, Jelena; Petrović, Silvana; Drobac, Milica; Tadić, Ivana (Archives of Pharmacy, 2022)
The use of medicinal plants has significant impact on human health (1,2). Approximately 13.000 medicinal plants are used worldwide, and in developing countries 65-80% of the population uses them for medicinal purposes. The aim of the study was to examine the awareness of patients in the city of Belgrade about herbal products. Quantitative, non-experimental research was conducted using a purpose-built questionnaire in public pharmacies during February 2020. The survey involved 954 respondents, mostly women (66.5%); 39.1% of respondents aged 20-40 years. Most of the respondents were employed (65.2%), with secondary school education (45.2%). The vast majority (97.3%) used medicinal plants/herbal products, mostly occasionally, as needed (38.4%). The main motive for their use was health improvement (75.2%), while 16.2% used them to treat diseases. The primary sources of information on medicinal plants/herbal products are pharmacists (45.1%) and the media (24.2%). About a third of the respondents (37.3%) stated that they knew the difference between herbal medicinal products and dietary supplements. 52.9% of respondents claimed that herbal medicinal products are effective, but less than synthetic drugs, while 61.5% claimed that they are safe, but with certain side effects. A third of respondents (32.9%) had difficulty understanding instructions for use and they needed additional explanations. Majority (70.6%) received advice from a pharmacist when buying a herbal product. Pharmacists are health professionals who have adequate knowledge of medicinal plants/herbal products and have a key role in advising patients in order to implement the proper use of herbal medicinal and other herbal products.